Analysis of Fuel Supply Control (Palm Shell) Using EOQ Method in Pt. Charoen Pokphand Indonesia Tbk - Abdul Rasyid; Widawati, Enny; Bachtiar W , Marsellinus (Kirana Publisher (KNPub), 2022)
PT. Charoen Pokphand Indonesia Tbk. (Gorontalo) is still experiencing problems in managing fuel supply where the company often experiences a lack of inventory that hinders the production process. The company also experienced excess inventory, causing storage costs to rise. For this reason, companies need to exercise inventory control. One of the analytical tools that can be used to control inventory is the